RNA-Seq-Based Whole Transcriptome Analysis of IPEC-J2 Cells During Swine Acute Diarrhea Syndrome Coronavirus Infection - Zhang, Fanfan; Yuan, Weifeng; Li, Zhiquan; Zhang, Yuhan; Ye, Yu; Li, Kai; Ding, Zhen; Chen, Yunyan; Cheng, Ting; Wu, Qiong; Tang, Yuxin; Song, Deping (Frontiers in Veterinary Science, 2020)
New emergence of swine acute diarrhea syndrome coronavirus (SADS-CoV) has resulted in high mortality in suckling pigs in China. Up to date, the transcriptional expression of host cells during SADS-CoV infection is not documented. In this study, by means of RNA-Seq technology, we investigated the whole genomic expression profiles of intestinal porcine epithelial cells (IPEC-J2) infected with a SADS-CoV strain SADS-CoV-CH-FJWT-2018. A total of 24,676 genes were identified in which 23,677 were known genes and 999 were novel genes. A total of 1,897 significantly differential expressed genes (DEGs) were identified between SADS-CoV-infected and uninfected cells at 6, 24, and 48 h post infection (hpi), and of which, 1,260 genes were up-regulated and 637 down-regulated. Gene Ontology enrichment analysis revealed that DEGs in samples from 6, 24, and 48 hpi were enriched in 79, 383, and 233 GO terms, respectively, which were mainly involved in immune system process, response to stimulus, signal transduction, and cytokine-cytokine receptor interactions. The 1,897 DEGs were mapped to 109 KEGG Ontology (KO) pathways classified in 4 main categories. Most of the DEGs annotated in the KEGG pathways were related to immune system, infectious viral disease and signal transduction. The mRNA of porcine serum amyloid A-3 protein (SAA3), an acute phase response protein, was significantly up-regulated during the infection. Over-expressed SAA3 in IPEC-J2 cells drasticaly inhibited the replication of SADS-CoV, while under-expressed SAA3 promoted virus replication. To our knowledge this is the first report on the profiles of gene expression of IPEC-J2 cells infected by SADS-CoV by means of RNA-Seq technology. Our results indicate that SADS-CoV infection significantly modified the host cell gene expression patterns, and the host cells responded in highly specific manners, including immune response, signal and cytokine transduction, and antiviral response. The findings provide important insights into the transcriptome of IPEC-J2 in SADS-CoV infection.